ANALYSIS OF THE REGISTRATION OF A LEGAL ENTITY NAME SUBSTANTIALLY SIMILAR TO THE REGISTERED TRADEMARK "CHANTIQUE" - Telaumbanua, Nathanael; Kansil, Christine S. T (Awang Long Law Review, 2024)
Over time, trademarks have come to play a significant role in businesses established by entrepreneurs. A trademark is defined as a graphical representation that can take the form of a logo, number, or letter. The presence of a trademark in a business provides a guarantee of quality and adds unique value that attracts consumers. However, it is not uncommon for other business actors to imitate trademarks in order to reap substantial benefits. Such actions are deemed unlawful as they harm other entrepreneurs striving to develop their businesses, thereby necessitating legal protection for the affected business actors. The type of research used is normative juridical research. Normative juridical research utilizes secondary data sources as well as legal book. The normative juridical research method is a legal research approach based on legal literature, legal books, and secondary data. Legal protection for trademarks is outlined in Law Number 20 of 2016 on Trademarks and Geographical Indications. According to this regulation, the process of registering a trademark must meet several requirements: it must possess distinctiveness, comply with statutory regulations, be publicly owned, and bear no direct relation to the goods or services being registered. These requirements must be fulfilled by entrepreneurs who wish to register their trademarks. Moreover, Indonesia adheres to a constitutive trademark registration system, where the individual with full rights to a trademark is the one who first registers it commonly referred to as the "first to file" principle. The purpose of this study is to examine the regulations and legal protections for legal entities that bear similarities to a registered trademark.